How Do Scholars Conceptualize and Conduct Health and Digital Health Literacy Research? Survey of Federally Funded Scholars - Mayank Sakhuja; Brooks Yelton; Simone Kavarana; Lauren Schaurer; Jancham Rachel Rumthao; Samuel Noblet; Michelle A Arent; Mark M Macauda; Lorie Donelle; Daniela B Friedman (JMIR Publications, 2024)
BackgroundThe concept of health literacy (HL) is constantly evolving, and social determinants of health (SDoH) have been receiving considerable attention in public health scholarship. Since a 1-size-fits-all approach for HL fails to account for multiple contextual factors and as a result poses challenges in improving literacy levels, there is a need to develop a deeper understanding of the current state of HL and digital health literacy (DHL) research. ObjectiveThis study examined scholars' conceptualization and scope of work focused on HL and DHL. MethodsUsing a search string, investigators (N=2042) focusing on HL, DHL, or both were identified from the grantee websites of the National Institutes of Health RePORTER (RePORT Expenditures and Results) and the Canadian Institutes of Health Research. The investigators were emailed a survey via Qualtrics. Survey questions examined the focus of work; whether the investigators studied HL/DHL in combination with other SDoH; the frameworks, definitions, and approaches used; and research settings. We analyzed survey data using SPSS Statistics version 28 and descriptive analysis, including frequencies and percentages, was conducted. Chi-square tests were performed to explore the association between the focus of work, settings, and age groups included in the investigators' research. ResultsA total of 193 (9.5%) of 2042 investigators responded to the online survey. Most investigators (76/153, 49.7%) were from public health, 83/193 (43%) reported their research focused on HL alone, 46/193 (23.8%) mentioned DHL, and 64/193 (33.2%) mentioned both. The majority (133/153, 86.9%) studied HL/DHL in combination with other SDoH, 106/135 (78.5%) conducted HL/DHL work in a community setting, and 100/156 (64.1%) reported not using any specific definition to guide their work. Digital tools (89/135, 65.9%), plain-language materials (82/135, 60.7%), and visual guides (56/135, 41.5%) were the top 3 approaches used. Most worked with adults (131/139, 94.2%) and all races and ethnicities (47/121, 38.8%). ConclusionsHL and DHL research largely considered SDoH. Multiple HL tools and approaches were used that support the examination and improvement of literacy and communication surrounding health care issues.